Genomic and proteomic characterization of the broad host range Salmonella phage PVP-SE1: the creation of a new phage genus - Santos, Sílvio Roberto Branco (2011)
(Bacterio)phage PVP-SE1, isolated from a German wastewater plant, presents a high potential value as a biocontrol agent and as a diagnostic tool, even compared to the well-studied typing phage Felix 01, due to its broad lytic spectrum against different Salmonella strains. Sequence analysis of its genome (145,964 bp) shows it to be terminally redundant and circularly permuted. Its G C content, 45.6 mol%, is lower than that of its hosts (50 to 54 mol%). We found a total of 244 open reading frames (ORFs), representing 91.6% of the coding capacity of the genome. Approximately 46% of encoded proteins are unique to this phage, and 22.1% of the proteins could be functionally assigned. This myovirus encodes a large number of tRNAs (n 24), reflecting its lytic capacity and evolution through different hosts. Tandem mass spectrometric analysis using electron spray ionization revealed 25 structural proteins as part of the mature phage particle. The genome sequence was found to share homology with 140 proteins of the Escherichia coli bacteriophage rV5. Both phages are unrelated to any other known virus, which suggests that an “rV5-like virus” genus should be created within the Myoviridae to contain these two phages.